Maintenance of red-tail coral snake (Micrurus mipartitus) in captivity and evaluation of individual venom variability (2016)
ABSTRACT: Red-tail coral snake (Micrurus mipartitus) is a long and thin bicolor coral snake widely distributed in Colombia and is the coral that causes the majority of accidents in the Andean region, so it is important to keep this species in captivity for anti-venom production and research. However, maintaining this species in captivity is very difficult because it refuses to feed, in addition to the high mortality rate due to maladaptation syndrome. In this study a force feeding diet, diverse substrates for maintenance and a milking technique were evaluated. Additionally, individual variability of the venom was determined by High Performance Liquid Chromatography (HPLC), Sodium Dodecyl Sulfate- Polyacrylamide Gel Electrophoresis (SDS-PAGE) and Coagulant, Anticoagulant and Hemolytic activities. The results of this study demonstrate that it was possible to increase the survival rate of this species in captivity and to determine some of the important factors in the maintenance. As to the individual variability of the venom, we found differences in number and intensity of peaks recovered by chromatography and also displayed variations in some of its biological activities.